2015
DOI: 10.1371/journal.pone.0128987
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokines, C-Reactive Protein, and Cardiovascular Disease: A Population-Based Prospective Study

Abstract: BackgroundBeing overweight or obese is associated with a greater risk of coronary heart disease and stroke compared with normal weight. The role of the specific adipose tissue-derived substances, called adipocytokines, in overweight- and obesity-related cardiovascular disease (CVD) is still unclear.ObjectiveTo investigate the associations of three adipose tissue-derived substances: adiponectin, leptin, and interleukin-6 with incident CVD in a longitudinal population-based study, including extensive adjustments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 44 publications
(62 reference statements)
1
30
0
2
Order By: Relevance
“…A published meta-analysis, comprising eight nested case-control studies with a total of 1980 CVD patients and 11567 participants, indicated a significant association between leptin and pathogenetic risk of CHD and stroke [21]. In contrast, the latest research studies did not find the same association [2224]. Given the inconsistency of prior results, we performed an updated meta-analysis to investigate the relationship between high leptin concentration and risk of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…A published meta-analysis, comprising eight nested case-control studies with a total of 1980 CVD patients and 11567 participants, indicated a significant association between leptin and pathogenetic risk of CHD and stroke [21]. In contrast, the latest research studies did not find the same association [2224]. Given the inconsistency of prior results, we performed an updated meta-analysis to investigate the relationship between high leptin concentration and risk of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…These findings provide a rationale to hypothesize that the plasma leptin/adiponectin (L/A) ratio is higher in subjects with low-normal thyroid function. Of note, the L/A ratio may represent a preferential marker compared to leptin and adiponectin alone in predicting incident cardiovascular disease [17, 18]. The L/A ratio is also considered to represent a biomarker of adipocyte dysfunction [19].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used inflammatory biomarker in established diabetes is highly selective Creactive protein (hs-CRP), which well correlates with CV complications, poorer metabolic control and severe hypoglycaemia in diabetes, although low sensitivity and specificity of this biomarker was found [11][12][13][14]. Apart from serial testing of hs-CRP, which is time-consuming, other novel pro-inflammatory biomarkers like Growth-Differentiation Factor-15 (GDF-15) have been proposed risk stratify patients with diabetes including type two diabetes mellitus (T2DM) [15].…”
Section: Introductionmentioning
confidence: 99%